2022
DOI: 10.1124/jpet.122.001289
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Cotransporter-2 Inhibition Exacerbates Hepatic Encephalopathy in Biliary Cirrhotic Rats

Abstract: In liver cirrhosis, hepatic inflammation and abundant portal-systemic collaterals are indicated for the development of hepatic encephalopathy. Sodium-glucose cotransporter-2 (SGLT-2) inhibitors are a type of anti-diabetic agent, which exert pleiotropic and anti-inflammatory effects. Diabetes and chronic liver disease often coexist but the influence of SGLT-2 inhibition on liver cirrhosis and hepatic encephalopathy remains unknown. This study investigated the effect of SGLT-2 inhibition on cirrhotic rats. Bilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Therefore, in view of the development of hepatic encephalopathy, patients with cirrhosis should be cautious about using empagliflozin. [41] Animal trials have shown that SGLT-2i has the risk of aggravating hepatic encephalopathy, and SGLT-2i is not necessarily a safe and effective hypoglycemic drug for T2MD patients with advanced NAFLD progression to cirrhosis complicated with hepatic encephalopathy. In a meta-analysis, it was noted that SGLT-2 inhibitors reduced hospitalizations for heart failure more than GLP-1 receptor agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in view of the development of hepatic encephalopathy, patients with cirrhosis should be cautious about using empagliflozin. [41] Animal trials have shown that SGLT-2i has the risk of aggravating hepatic encephalopathy, and SGLT-2i is not necessarily a safe and effective hypoglycemic drug for T2MD patients with advanced NAFLD progression to cirrhosis complicated with hepatic encephalopathy. In a meta-analysis, it was noted that SGLT-2 inhibitors reduced hospitalizations for heart failure more than GLP-1 receptor agonists.…”
Section: Discussionmentioning
confidence: 99%